Effects of fatigue on the lower limb biomechanics during single leg landing among male recreational athletes - Zahir, Muhammad Amzar Anas Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Most landing studies focused on several common biomechanical variables to characterize the role of different factors in injury. These variables include the joint kinematics and peak vertical Ground Reaction Force (vGRF). Peak vGRF may elaborate internal loads that may cause injury if not sufficiently distributed or attenuated by the musculoskeletal system. Furthermore, many studies have been conducted on the biomechanics of landing to determine the biomechanical factors that can minimize the impact forces and knee loading during landing. However, studies about the effects of fatigue on lower limb biomechanics during single leg landing (SLL) are scarce. Therefore, this study has been conducted to know the effects of fatigue on the lower limb biomechanics during SLL among male recreational athletes (i.e., volleyball, basketball, handball, and badminton). Fifteen participants joined the study voluntarily. Thirteen of them were recruited after anthropometrical screening. The participants performed Single Leg Landing (SLL) test (i.e., maximal effort countermovement jump from the ground) with three-dimensional (3D) motion capture before and after performing the fatigue protocol. During the fatigue protocol, participants were considered to achieve fatigue when their heart rate (HR) reached 90% of their age-calculated maximum heart rate, or when they cannot continue to perform rope skipping anymore. The sagittal plane knee joint kinematics and GRF was evaluated using the Qualisys Motion Capture Systems. The kinematics and GRF were compared at three landing phases (i.e., Maximum vGRF, 1st peak, and 2nd peak of vGRF). Paired T-test and Wilcoxon-Signed Rank test were used in this study to know if there were any significant differences in knee kinematics and GRF between pre- and post-fatigue. Based on the tests, there were no significant effects of fatigue on sagittal plane knee kinematics at all landing phases. For GRF, there were no significant effects of fatigue on the vGRF at landing phases 1st peak and 2nd peak of vGRF, however, there was significant effect of fatigue on the vGRF at landing phase maximum vGRF (MvGRF). Therefore, coaches and athletes are suggested to include more training that focuses on the correction of landing technique. For kinematics, coaches should focus on the improvement of knee flexion angle during landing with single leg, while for GRF, coaches should focus on the dissipation of forces at the knee.